Estrategias de marketing digital en la Veterinaria Alina del sector Mata de Cacao de la parroquia de Febres cordero, periodo 2023. - Bajaña Vera, Andy Rodrigo (2024)
This case study is prescribed in order to provide an analysis regarding the strategic importance of a digital marketing plan in the Alina veterinary pharmacy company that would strengthen the business as such by being able to establish itself as a positioned and preponderant business in the commercial market. through advertising promotions and strategies on digital pages and social networks, etc. The case study is directed with the line of research based on Information and Communication Systems, Entrepreneurship and Innovation and is correlated through the Marketing and Commercialization subline, and, on the other hand, is defined with the linkage activities with the pre-professional internship project, referring to the Application of Administrative or Commercial Processes in the Public and Private sector. In this study, survey models were applied to the target audience of the sector in order to assess the importance of marketing in the business and the impact it would have on the user who is related to this medium and business model. On the other hand, the importance of the needs of today's market and its trends that exist in users on the commerce of companies using digital marketing tools is evaluated. In addition, it offers the company to establish itself as a company that stands out in the market through new forms of commerce and sales positioning perspectives, in addition to finding new important markets through these current designs.